Western Diet Consumption During Development: Setting the Stage for Neurocognitive Dysfunction - Tsan, Linda; Décarie-Spain, Léa; Noble, Emily E.; Kanoski, Scott E. (Frontiers in Neuroscience, 2021)
The dietary pattern in industrialized countries has changed substantially over the past century due to technological advances in agriculture, food processing, storage, marketing, and distribution practices. The availability of highly palatable, calorically dense foods that are shelf-stable has facilitated a food environment where overconsumption of foods that have a high percentage of calories derived from fat (particularly saturated fat) and sugar is extremely common in modern Westernized societies. In addition to being a predictor of obesity and metabolic dysfunction, consumption of a Western diet (WD) is related to poorer cognitive performance across the lifespan. In particular, WD consumption during critical early life stages of development has negative consequences on various cognitive abilities later in adulthood. This review highlights rodent model research identifying dietary, metabolic, and neurobiological mechanisms linking consumption of a WD during early life periods of development (gestation, lactation, juvenile and adolescence) with behavioral impairments in multiple cognitive domains, including anxiety-like behavior, learning and memory function, reward-motivated behavior, and social behavior. The literature supports a model in which early life WD consumption leads to long-lasting neurocognitive impairments that are largely dissociable from WD effects on obesity and metabolic dysfunction.